PENGARUH MOTIVASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI KECAMATAN CIMALAKA KABUPATEN SUMEDANG - Teddy Marliady Nurwan (LPPM UNSAP & FISIP UNSAP, 2017)
Research in Cimalaka District, Sumedang Regency, To obtain an assessment of work in the Cimalaka District Office, Sumedang Regency, To obtain information about motivation by working together in the Cimalaka District Office, Sumedang Regency, to be enjoyed. working in the Cimalaka District Office of Sumedang Regency. Participating in this study were all Cimalaka District Sumedang District employees who gathered 35 employees. In this study the authors used a saturated sample technique, because the study sample was relatively small at 35 people, so that all studies were sampled. In this study the authors used a saturated sample technique, because the study sample was relatively small at 35 people, so that all studies were sampled. Motivation in Cimalaka Subdistrict, Sumedang Regency has not run well seen in the respondents' answers on average by 51.80%. Employee work productivity in Cimalaka Sub-District, Sumedang Regency has not yet achieved good results because the research reached an average of 52.79%. The correlation between motivation and employee productivity in Cimalaka Sub-District, Sumedang District, the coefficient value is 0.94 depending on the category of very strong and significant related to the strong relationship between Motivation and employee workforce in Cimalaka Sub-district, Sumedang District. The influence of motivation on employee productivity in Cimalaka District reached 88.36%. the remaining 11.64% is influenced by other factors such as the quality factor of Human Resources (HR), internal communication, supervision and leadership and others.